A parser generator system to handle complete syntax - Ossher, Harold Leon (Rhodes University, Faculty of Science, Department of Computer Science, 1982)
To define a language completely, it is necessary to define both its syntax and semantics. If these definitions are in a suitable form, the parser and code-generator of a compiler, respectively, can be generated from them. This thesis addresses the problem of syntax definition and automatic parser generation.
Keywords: Grammar, Comparative and general -- Syntax; Parsing (Computer grammar); Programming languages (Electronic computers); Compilers (Computer programs)